Heterogeneity of plasmids determining high-level resistance to gentamicin in clinical isolates of Streptococcus faecalis. - Zervos, M J (1986)
Between November 1981 and October 1984, 48 of 3,458 clinical isolates of Streptococcus faecalis at the University of Michigan Hospital showed high-level (greater than 2,000 micrograms/ml) resistance to gentamicin, as well as to all other clinically available aminoglycosides. Thirteen percent of clinical isolates in the University of Michigan Hospital currently demonstrate this level of resistance. Transfer of resistance to a plasmid-free streptococcal recipient was observed in filter matings for 44 of 48 such isolates. Analysis of transconjugants by agarose gel electrophoresis showed that gentamicin resistance was transferred alone in 8 isolates and was combined with other antimicrobial resistances on the same plasmid in the other 36 isolates. There were seven isolates which transferred the property of horse blood beta-hemolysis along with gentamicin resistance. Transfer of gentamicin resistance was either by conjugative plasmids or by a nonconjugative but mobilizable plasmid. Transfer frequencies on filters ranged from 4.7 X 10(-2) to 4.1 X 10(-8). Based on donor and transconjugant antibiotic resistance markers, agarose gel electrophoresis, transfer properties, and restriction enzyme analysis, the plasmid content of transconjugants was heterogeneous and could be classified into at least seven different patterns. These findings argue against clonal dissemination as the cause of the increased frequency of resistant strains and suggest that resistance to gentamicin appears on a variety of physically distinct conjugative and nonconjugative plasmids in S. faecalis.